IP Conflicts in the Music Industry: The Misuse of Sampling from a Copyright Perspective : English - Galang Farel; Meita Fadhilah (jurnal.unprimdn.ac.id, 2026)
Intellectual Property Rights (IPR) conflicts in the music industry, focusing on the misuse of sampling that often leads to legal disputes. Sampling, as a modern music creation technique, carries artistic value, yet its use frequently clashes with copyright protection. This study employs a normative legal method through statutory approaches and case analyses. The findings indicate that sampling without permission from the copyright holder has the potential to infringe both the moral and economic rights of the creator, thereby leading to legal consequences. These results emphasize the importance of a deeper understanding of copyright regulations among music industry actors in order to achieve a balance between creative freedom and the protection of intellectual property rights.